2017
DOI: 10.1093/infdis/jix095
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel CD206+ Macrophage-Specific Arterial Imaging Strategy in HIV-Infected Individuals

Abstract: NCT02542371.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Several radioligands, including those targeting inducible nitric oxide synthase (21), folate receptor-b (22,23), CD206 (24,25), and LOX-1 (26)(27)(28), have been developed to visualize macrophages, and several of these have also been used to image acute inflammation. Though present ubiquitously, TSPO expression is elevated in immunologically activated leukocytes such as microglia and macrophages (29) and has been used as a molecular target for imaging of neuroinflammation (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Several radioligands, including those targeting inducible nitric oxide synthase (21), folate receptor-b (22,23), CD206 (24,25), and LOX-1 (26)(27)(28), have been developed to visualize macrophages, and several of these have also been used to image acute inflammation. Though present ubiquitously, TSPO expression is elevated in immunologically activated leukocytes such as microglia and macrophages (29) and has been used as a molecular target for imaging of neuroinflammation (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…We previously have described increased arterial inflammation in PWH and how this could also contribute to the increased risk of CVD among PWH [ [33] , [34] , [35] ]. Within the INTREPID trial, in turn, we previously demonstrated significant reduction with statin therapy of a systemic marker of arterial inflammation — Lp-PLA2 [ 7 ] — which has been associated with increased CVD in the general population [ 36 ] and among PWH [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated immune cells also contribute to plaque remodeling, promoting the development of high-risk morphology plaque features which predispose to atherothrombosis(8). In studies focused on MLHIV, systemic markers of monocyte activation have been related to arterial inflammation(9, 10), subclinical carotid and coronary artery atherosclerosis(1114), and pathologically remodeled coronary atherosclerotic plaque(15, 16). Studies focused predominantly on WLHIV have revealed relationships between systemic immune markers and carotid atherosclerosis(1719), as well as the percent of non-calcified coronary atherosclerotic plaque(6).…”
Section: Systemic Immune Activation/ Inflammation and Hiv-associated mentioning
confidence: 99%
“…Specific links between systemic immune activation markers and neurocognitive impairment have also been drawn among WLHIV, even those who are well-treated with ART and have undetectable serum viral load(36). Just as arterial inflammation and myocardial inflammation have been quantified by non-invasive imaging studies among people living with HIV (PLHIV) with CVD risk factors(9, 10, 25), neuroinflammation has also been quantified by non-invasive imaging studies among individuals with HIV and neurocognitive impairment(37). …”
Section: Systemic Immune Activation/ Inflammation and Hiv-associated mentioning
confidence: 99%